Real-world effectiveness of erenumab in Japanese patients with migraine - Keisuke Suzuki; Shiho Suzuki; Tomohiko Shiina; Yasuo Haruyama; Saro Kobayashi; Mukuto Shioda; Koichi Hirata (Heliyon, 2024)
Background: Real-world evidence of erenumab effectiveness in migraine patients in Asia with various comorbidities and multiple previous medication failures is still limited. Methods: A 6-month single-center cohort study of 45 patients with episodic or chronic migraine (CM) treated with erenumab was conducted. In the cohort, 60.0% were switching from other calcitonin gene-related peptide monoclonal antibodies (CGRP mAbs), and 66.7% had ≥4 prophylaxis failures. The change in monthly migraine days (MMDs) from baseline and percentages of responders after treatment were calculated. Weekly migraine days (WMDs) were obtained at baseline and at months 1, 2 and 3 and were compared between weeks 2 and 4. Results: In total, 36%, 47%, and 63% of patients had a ≥30% response at 1, 3, and 6 months, respectively. The cumulative percentage of patients achieving a ≥30% response over 6 months was 85%. Early responders (average ≥ 30% response at 1–3 months) accounted for 37.8%, 55.6%, and 25.9% of the total, CGRP mAb-naïve, and CGRP mAb-switching groups, respectively. Late responders (average < 30% response at 1–3 months and average ≥ 30% response at 4–6 months) accounted for 46.4%, 37.5%, and 58.8% of nonearly responders in the total, CGRP mAb-naïve, and CGRP mAb-switching groups, respectively. Mild adverse reactions were observed in 5 patients (11.1%). Wearing-off, defined as an increase in the number of WMDs ≥2 between week 2 and week 4, was observed in 2.4–12.5% at months 1–3. Conclusion: Erenumab was effective in migraine patients. At least 4–6 months may be preferable for efficacy evaluation in patients switching to erenumab from other CGRP mAbs.